Fenton reaction by H2O2 produced on a magnetically recyclable Ag/CuWO4/NiFe2O4 photocatalyst. Issue 8 (16th March 2023) - Kumar, Uttam; Shrivastava, Anshu; De, Arup Kumar; Pai, Mrinal R.; Sinha, Indrajit
Abstract : The development of recyclable H2 O2 -producing photocatalysts with in situ Fenton-like organic pollutant degradation is currently a topical area of research. Abstract : The development of recyclable H2 O2 -producing photocatalysts with in situ Fenton-like organic pollutant degradation is currently a topical area of research. This research investigates the visible light photocatalytic formation of H2 O2 on Ag/CuWO4 /NiFe2 O4 composites. Investigations revealed that NiFe2 O4 and CuWO4 have staggered valence band (VB) and conduction band (CB) positions, with the former acting as the reduction component. Large-scale molecular dynamics simulations demonstrated that oxygen molecules (in an aqueous medium) have an affinity for the NiFe2 O4 surface. Appropriate scavenger experiments and molecular dynamics results point to a Z-scheme mechanism. Substantial H2 O2 formation occurred on continuous oxygen-passing through the aqueous reaction medium under visible light irradiation in pure water. This H2 O2 successfully degraded tetracycline by an in situ (heterogeneous) Fenton-like reaction.